SULTAN MAHMUD BADARUDDIN II (SMB II): KAJIAN SEJARAH DAN ARKEOLOGI ISLAM KESULTANAN PALEMBANG DARUSSALAM - Andhifani, Wahyu Rizky; Ali, Nor Huda, NHA (UI Scholars Hub, 2026)
The intellectual, architectural, and artifactual heritage of the Palembang Darussalam Sultanate during the reign of Sultan Mahmud Badaruddin II (1767–1852) is examined in this study using a historical archaeological approach and textual analysis of manuscripts, buildings, and royal tombstones. This study assumes that Palembang functions as a political force and a centre of Islamic-Malay knowledge. The results show that the Palembang palace functioned as an epistemic space that combined religious understanding (tafaqquh fi al-dīn) and Islamic nobility, as evidenced by religious works such as the Syair Burung Nuri and legal documents (piyagêm) written in the Palembang script. The architecture of the Palembang Grand Mosque and the Kuto Besak Palace combines Islamic cosmological symbolism with local aesthetics and influences from various cultures. Meanwhile, places like Benteng Sungai Aur and the Kawah Tengkurep tomb complex demonstrate the close relationship between spirituality and defence tactics, making these places dynamic environments of Islamization. Historically, SMB II is depicted as a symbol of resistance against colonialism and the protector of Islamic civilisation, upholding morality, art, and science amidst imperialist pressure. This study shows that the heroism of SMB II was not only material but also spiritual. This is a type of archaeological power that uses faith, knowledge, and cultural legitimacy to maintain Islamic civilisation in the Nusantara.